Post-herpetic neuralgia: A review of current management strategies - Saru Singh; Ruchi Gupta; Sukhdeep Kaur; Jasleen Kaur (Indian Journal of Pain, 2013)
Post herpetic neuralgia (PHN) is a chronic neuropathic pain in the region of the herpes zoster (HZ) rash, persisting after the cutaneous lesions have healed. Despite numerous treatment advances, many patients remain refractory to the current therapies and continue to have pain, physical and psychological distress. In this review, we will discuss the current strategies for prevention and management of this disease, as also the insight into the future probabilities.